Of The Artistic Discourse Of Orientalism." - Alaa Abdel Monem, Ibrahim (El Omda in Linguistics and Discourse Analysis, 2025)
transforms them into elusive visual texts that align with the principles of evasion, ambiguity, and the deferral of meaning, generating derivatives such as postponement, contradiction, and the infinite nature of signification. Orientalism - Cultural Criticism - Representation - Cultural Syste